Moyens juridiques en cas d’inexécution des obligations dans le Code Civil de la République de Moldavie [Articol] - Băieşu Aurel (Editura USM, 2025)
This article is devoted to the reformation of the Civ. Code R.M. and of the regulations governing legal remedies in cases of non-performance of an obligation. This reformation is aimed to modernize the national legal framework governing the area of contract law and to the nation’s law in line with the most recent regulations. The reform was accomplished by incorporating the most advanced legislative and academic achievements of the previous decades, which resulted in the fact that the regulations under consideration at this time constitute a unique and coherent system of legal remedies available to creditors in the event of non-performance of contractual obligations. The unitary regulation of the remedies for non- performance of the contract in a single chapter of the Civil Code of the Republic of Moldova, which brought together the related regulations previously dispersed in different sections of the Code, will make it easier for the creditor of an unexecuted obligation to perceive the possibilities offered by the law and to allow the creditor to choose the legal remedy that best corresponds to their interests.
Keywords: civil code; contractual obligation; legal remedy; termination; damages; European law; contract law